PERKEMBANGAN PESERTA DIDIK DALAM AL-QUR`AN ( Telaah Psikologi Perkembangan ) - Kasnun, Kasnun (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
This paper tries to describe the phases of human development in terms of various dimensions, and in addition, it is compared with the phases of human education in Al-Qurâan. Through this comparison, it is expected that the periodicity of education can be criticized, whether or not it is in line with the demands of each phase and then find out the solution for the development of education in the future. Individuals might never be in static condition or circumstance; they always experience a change in themselves. In the field of education, this change is supposed to be the crux of the matter. Therefore, educator must be aware how the process of development happens, what are the factors that influence it, and how are the individual traits during a particular development. This notion is crucial to understand in order that educators can act and behave rationally and proportionally in accordance with the psychological state of individuals due to the fact that the core of the education process is to stimulate and give direction towards the change with the development of individuals that is aspired to education.ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© ØªÙØ¯ÙÙ ÙØ±Ø§ØÙ ÙÙÙ Ø§ÙØ§ÙØ³Ø§Ù ÙÙ ÙØ®ØªÙÙ Ø¬ÙØ§ÙØ¨Ù Ø«Ù ÙÙØ§Ø±ÙØªÙØ§ Ø¨ØªØ±Ø¨ÙØ© Ø§ÙØ¥ÙØ³Ø§Ù ÙÙ Ø¶ÙØ¡ Ø§ÙÙØ±Ø¢Ù. ÙØ±Ø¬Ù ÙÙ ÙØ±Ø§Ø¡ Ø§ÙÙÙØ§Ø±ÙØ© Ø§ÙÙØ§Ù ØªÙØªÙØ´ ÙØ±Ø§ØÙ Ø§ÙØªØ±Ø¨ÙØ© ÙÙ ÙÙ ÙÙØ§Ø³Ø¨Ø© Ø¨ÙØªØ·ÙØ¨Ø§Øª ÙÙ ÙØ±ØÙØªÙØ§ ØØ Ø«ÙÙ Ø§ÙØ§ØªÙØ§Ù Ø¨ØÙÙÙÙØ§ ÙØªØ±ÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© ÙØªÙÙÙØªÙØ§ ÙÙ Ø§ÙÙØ³ØªÙØ¨Ù. ÙÙØ§ ÙØ«Ø¨Øª ÙÙ Ø¥ÙØ³Ø§Ù ÙÙ ÙÙÙÙ ÙØ§ØØ¯ Ø¨Ù ÙØªØºÙÙØ± Ø¯Ø§Ø¦ÙØ§. ÙØ§ÙØªØºÙÙØ± ÙÙ Ø§ÙØ¥ÙØ³Ø§Ù ÙÙ ÙØ³Ø£ÙØ© ÙÙÙØ© ÙÙ Ø§ÙØªØ±Ø¨ÙØ©. ÙØ¹ÙÙ Ø§ÙÙØ¯Ø±Ø³ Ø£Ù ÙÙÙÙÂ  ÙÙÙ ØªÙØ¹ ÙØ°Ù Ø§ÙØªØºÙÙØ±Ø§Øª Ø¬ÙØ¯Ø§Ø ÙÙØ§ Ø§ÙØ¹ÙØ§ÙÙ Ø§ÙÙØ¤Ø«Ø±Ø© ÙÙÙØ§Ø ÙÙÙÙ ÙÙØ§ØµÙØ§Øª Ø§ÙÙØ±Ø¯ ÙÙ ÙÙ ÙØ°Ù Ø§ÙÙØªØ±Ø© ÙÙ Ø§ÙØªØ¬Ø¯ÙØ¯ ÙØ§ÙØªØºÙÙØ±. ÙØ°Ø§ ÙÙÙØ¯Ø± Ø§ÙÙØ¯Ø±Ø³ Ø§ÙØ¹ÙÙ Ø¨ÙØ§ ÙÙØ§Ø³Ø¨ ØØ§ÙØ© ÙÙØ³ÙØ© Ø§ÙØªÙØ§ÙÙØ°. ÙÙØ°ÙÙ ÙÙÙ Ø§ÙÙØ¯Ø±Ø³ Ø¹Ù ÙÙÙÙØ© ÙÙÙØ¹ Ø¹ÙÙÙØ© ÙØ°Ø§ Ø§ÙØªØ·ÙØ±Ø ÙØ£Ø³Ø¨Ø§Ø¨ÙØ§ Ø§ÙÙØ¤Ø«Ø±Ø© ÙÙÙÙ ÙÙØ§ØµÙØ§Øª Ø§ÙÙØ±Ø¯ ÙÙ ÙØ±ØÙØ© Ø§ÙØªØ·ÙØ± Ø£ÙØ± ÙØ§Ø¨Ø¯Ù ÙÙÙØ ÙØ£ÙÙ ÙÙØ§Ø© Ø§ÙØªØ±Ø¨ÙØ© ÙÙ Ø§ÙÙØØ§ÙÙØ§Øª ÙØ§ÙØ¯ÙØ¹ ÙØªÙØ¬ÙÙ Ø§ÙØªØºÙÙØ± ÙÙÙØ§Ø³Ø¨ ØªØ·ÙØ± Ø§ÙÙØ±Ø¯ Ø§ÙÙØ±Ø¬Ù ÙÙ Ø§ÙØªØ±Ø¨ÙØ©.Â